(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Sustainable phyto medicine drug discovery has emerged as a promising strategy for addressing global healthcare challenges while minimizing environmental impact. Eco-friendly approaches integrate green extraction technologies, renewable plant resources, metabolomics, computational biology, artificial intelligence, and environmentally benign manufacturing processes to accelerate the discovery of safe and effective phototherapeutic agents. These strategies reduce the use of hazardous solvents, improve resource efficiency, and enhance the quality, reproducibility, and scalability of herbal products. Advances in phytochemical profiling, bioactivity-guided isolation, molecular docking, and systems pharmacology have strengthened the scientific validation of medicinal plants and facilitated the identification of novel lead compounds. Furthermore, sustainable cultivation practices, quality standardization, and regulatory compliance contribute to the development of reliable phytomedicines with consistent therapeutic performance. The integration of green chemistry principles with modern pharmaceutical research supports the development of safer medicines while preserving biodiversity and promoting responsible utilization of medicinal plant resources. Despite significant progress, challenges such as raw material variability, standardization, clinical validation, and global regulatory harmonization remain. Future interdisciplinary research combining sustainable technologies with precision medicine is expected to enhance therapeutic outcomes and expand the global acceptance of evidence-based phytomedicines. Sustainable phytomedicine drug discovery therefore represents a vital pathway toward environmentally responsible healthcare and improved patient well-being.